Mental health malleability beliefs and help-seeking intentions among Chinese college students: the mediating role of help-seeking self-stigma and the moderating role of depression - Chen, Wenbo; Dang, Junhua (Frontiers in Psychology, 2026)
IntroductionCollege years represent a critical period for mental health; however, despite the high prevalence of depression among them, Chinese college students show low utilization of on-campus mental health services. This study examined the associations between beliefs about the malleability of mental health, help-seeking self-stigma, depression level, and intentions to seek mental health services on campus among Chinese college students.MethodA sample of 2,258 Chinese undergraduates (589 males and 1,669 females, aged between 18 and 25 years old; Mage = 19.59, SD = 1.23) completed questionnaires measuring the core variables, including Implicit Theories of Mental Health Scale, Help-Seeking Self-Stigma Scale, Intentions to Seek Mental Health Services on Campus, and Patient Health Questionnaire. A moderated mediation model was developed to analyze the beliefs about the malleability of mental health, help-seeking self-stigma, depression level, and intentions to seek mental health services on campus.ResultsThis study showed that (1) beliefs about the malleability of mental health were positively associated with intentions to seek on-campus services (b = 0.44, p < 0.001, 95% CI [0.22, 0.66]); (2) help-seeking self-stigma partially mediated this association between beliefs about the malleability of mental health and intentions to seek on-campus services, with an indirect effect value of 0.19, 95% CI [0.15, 0.25] and accounting for 30.51% of the total effect; (3) depression level marginally significantly moderated the first stage of the mediating pathway(interaction term b = 0.01, p < 0.05, 95% CI [0.0004, 0.02]). Specifically, the negative association between beliefs about the malleability of mental health and self-stigma was weaker among students with higher depression levels.DiscussionThis findings showed that beliefs about the malleability of mental health were positively associated with Chinese college students’ intentions to seek on-campus mental health services by reducing help-seeking self-stigma, and this mediating effect is weakened among students with higher depression levels. These findings provide insights into factors facilitating the utilization of on-campus mental health services and inform targeted interventions to reduce help-seeking self-stigma.